Analisis Faktor yang Mempengaruhi Keputusan Nasabah dalam Pengambilan Produk Rahn di Pegadaian Syariah Cabang Kota Solok - Salsabilla Dumia Putri; Dewi Manda Angraini (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research is motivated by the large number of customers who are interested in using pawn products (rahn), this is because people's needs continue to increase for additional business capital, while the funds they have are limited. However, with increasing community needs, pawnshops themselves are not providing optimal services to customers. However, due to the lack of service received by customers, they still choose Rahn products. So, this research aims to find out the factors that influence customer decisions in picking up Rahn products at the Solok City Branch Sharia Pawnshop and to find out the most dominant factors that influence customer decisions in picking up Rahn products at the Solok City Branch Sharia Pawnshop. This research is quantitative research. The data collection tool uses a questionnaire. The population of this research is all customers who use rahn at the Solok branch of the sharia pawnshop in 2024, totaling 18,033 respondents with a sample of 100 respondents. The data analysis technique in this research uses research instrument tests, prerequisite tests and factor analysis tests with the help of SPSS. Based on the results of research that has been carried out, the results show that there are four factors that influence customers' decisions in purchasing rahn products, namely promotional factors, price factors, sharia aspect factors and location factors. Then the most dominant factor of the four factors that influence customers' decisions in taking Rahn products is the price factor.